Criteria validity of the Netherlands physical activity questionnaire for children - Vinicius de Oliveira Damasceno; André Scotti Rabelo; Joel Alves Lamounier; Leszek Antoni Szmuchrowski; Bruno Pena Couto; Danilo Edson de Souza; Reginaldo Gonçalves (Universidade Federal de Santa Catarina, 2018)
Physical activity measurement with accuracy and precision is extremely important in establishing the dose-response relationship between levels of physical activity and the different outcome possibilities. Subjective methods of measurement, such as proxy-reports have been used as a possibility to check physical activity in children. The aim of this study was to test the Netherlands Physical Activity Questionnaire (NPAQ), valid for Brazilian schoolchildren using physical aerobic fitness as a criterion. The study included 290 children aged 6-10 years from public schools of Itaúna/MG. NPAQ was applied to parents or guardians and children were tested using the Luc Léger test. NPAQ had mean score of 25 for children (25 for boys and 24 for girls) and VO2max was 50.8 ml/kg/min for children (52.6 and 50.2 ml/kg/min for boys and girls, respectively). The Spearmam correlation test showed significant correlation (rsho = 0.146; p = 0.013) between NPAQ and VO2max, but the correlation is weak (Kappa -0.14). The results showed that NPAQ presented poor construct validity for physical activity measurement in a Brazilian schoolchildren sample, based on aerobic physical fitness criteria.